Pengaruh Kegiatan Formal dan Nonformal Terhadap Pembentukan Karakter Siswa dalam Menghadapi Tantangan Degradasi Moral di Era Digital - David Anggara; Anis Refimuti; Rio Dimas Prasetya; Asep Kusmawan (Institusi Agama Islam Negeri (IAIN) Bone, 2026)
The effect of formal and nonformal activities on students’ character formation in facing moral degradation in the digital era is examined using a quantitative explanatory approach. The study involved 279 students selected through simple random sampling, with data collected using Likert-scale questionnaires and analyzed through multiple linear regression. The findings indicate that formal activities have a positive and significant effect (? = 0.412; t = 6.149; Sig. < 0.05), while nonformal activities show a more dominant influence (? = 0.465; t = 7.266; Sig. < 0.05). Simultaneously, both variables significantly affect character formation (F = 68.215; Sig. < 0.05) with a contribution of 33.1% (R² = 0.331). The mean scores reveal that formal (4.23) and nonformal activities (4.31) are categorized as very good, while students’ character (4.16) is categorized as good. It can be concluded that integrating formal and nonformal activities is an effective strategy to strengthen students’ character, where formal education provides conceptual foundations and nonformal activities enhance value internalization through practical experiences in the digital era.